Assessment of the genotoxic potential of water courses impacted by wastewater treatment effluents using micronucleus assay in plants from the species Tradescantia. Issue 13 (3rd July 2019) - Campos, Carlos Fernando; Morelli, Sandra; De Campos Júnior, Edimar Olegário; Santos, Vanessa Santana Vieira; De Morais, Cássio Resende; Cunha, Matheus Campos; Souto, Henrique Nazareth; Pavanin, Luiz Alfredo; Bonetti, Ana Maria; Pereira, Boscolli Barbosa
ABSTRACT: Water pollution and the increase in genotoxic consequences in aquatic environments are well documented indicating the necessity and importance of biomonitoring programs. The objective of the present study was to determine the environmental quality of water resources and genotoxic potential of materials present within water samples obtained from the Perdizes River and the Mumbuca Stream, located in a region of discharge of wastewater treatment effluents using Tradescantia micronucleus assay (Trad – MCN). Water samples were collected from different locations up and downstream of the wastewater treatment plant during rainy season and subsequently submitted to physico-chemical analysis and Trad-MCN bioassay. The spatial distribution of the physico-chemical parameters assessed suggested that discharges of wastewater treatment effluents reduced water quality at all sites examined. Further, exposure to wastewater treatment effluents produced genotoxic effects on tetrads of Tradescantia pallida . These results reinforce the sensitivity of the Trad-MCN bioassay and its potential application in water quality monitoring programs concomitant with physicochemical evaluation.